Efek Sisa Pupuk Kandang Diperkaya Fosfat Alam terhadap Produksi Jagung Manis dan Jerami di Lahan Kering - Dwi Retno Lukiwati; R.I. Pujaningsih (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2014)
Manure enriched by rock phosphate (RP) and inoculated with biodecomposer very important to improve the upland fertility. Residual effects of applied manure can be used for the next growing season. The objective of the research was to investigate the residual effects of some kind of manure on sweet corn (Zea mays saccharata), dry matter (DM) and P production of stover on second growing season. A field experiment of completely randomized design with 7 treatments and four replicates. Level of P (RP), N (urea) and K (KCl) fertilizers was 66 kg P/ha, 200 kg N/ha, and 125 kg K/ha, respectively. All of manure application at 30 ton/ha and enriched with RP. The treatments at the first growing season were T0 (manure), T1 (manure +EM4), T2 (manure+starTmik), T3 (manure +stardec), T4 (manure granular+EM4), T5 (manure granular+starTmik), and T6 (manure granular+stardec). The sweet corn was harvested at 70 days, the stover was cut and measured for DM and P production. The result showed that effect of some kind of manure was not significantly different to sweet corn and DM production. Manure inoculated with biodecomposer resulted in signficantly higher of P production than without biodecomposer. Conclusion, all of manure resulted in similar on sweet corn and DM, except manure inoculated with biodecomposer resulted in higher of P production than without biodecomposer.